2022
DOI: 10.3389/fnagi.2022.878276
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing food molecules as a potential BACE1 inhibitor for Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a severe neurodegenerative disorder of the brain that manifests as dementia, disorientation, difficulty in speech, and progressive cognitive and behavioral impairment. The emerging therapeutic approach to AD management is the inhibition of β-site APP cleaving enzyme-1 (BACE1), known to be one of the two aspartyl proteases that cleave β-amyloid precursor protein (APP). Studies confirmed the association of high BACE1 activity with the proficiency in the formation of β-amyloid-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Molecular dynamics (MD) simulation is reliably used for the analysis of atomic behavior, structural stability, and conformational changes at the atomic level of a protein [ 23 , 24 ]. In this study, the synergistic interactions of curcumin and plumbagin with the target proteins were further investigated by performing an MD simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulation is reliably used for the analysis of atomic behavior, structural stability, and conformational changes at the atomic level of a protein [ 23 , 24 ]. In this study, the synergistic interactions of curcumin and plumbagin with the target proteins were further investigated by performing an MD simulation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Cα-backbone of the target protein bound to curcumin (PI3K-C) showed a deviation of 3.9 Å. Interestingly, the consortia of plumbagin and curcumin bound to PI3K protein (PI3K-C-P) exhibited a very stable RMSD of 2.3 Å. A stable RMSD plot during simulation signifies good convergence and stable conformations [ 23 , 25 , 26 , 27 ]. Therefore, it can be suggested that PI3K forms a quite stable complex when subjected to synergistic binding with plumbagin and curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing the overactive inflammatory response has been shown in these studies to have beneficial effects on health and lifespan. These results suggest that TLR4 inhibitors may have therapeutic potential [ 13 , 14 ]. The repurposing anti-diabetic drugs as a long-term remedy to the condition with which they are associated is evidently an accurate choice.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we established the capacity of presently available diabetic drugs to bind to TLR4 and block it from activating using computational biology. This was finished in harmony with the standards of the US Food and Drug Administration [ 12 , 13 , 15 ]. Therefore, a exceptional technique of treating AD with a single drug has been revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation